EFISIENSI PEMASARAN BENIH IKAN AIR TAWAR DI DESA MARGACINTA KECAMATAN MORAMO KABUPATEN KONAWE SELATAN - Riyan Budiyanto; Roslindah Daeng Siang; Ruslaini; Irdam Riani; Risfandi (UNPERBA, 2026)
This study aims to analyze the marketing efficiency of fresh water fish seeds from Margacinta Village, Moramo District, Konawe Selatan Regency. The types of fish cultivated are catfish, gourami, goldfish and koi. The data collection technique was through interviewers on 4 hatchery business actors, 2 inverting traders and 4 enlargement cultivators. Data were analyzed with a quantitative descriptive approach. The results showed that there were two marketing channel patterns for freshwater fish fry, namely channel I for hatchery-large-growing cultivators and channel II for hatchery-trader complementing-large-growing cultivators. Freshwater fish seed marketing in marketing channels I and II is categorized as efficient because the value of the farmer's share is ≥ 50%. In channel I the value for farmers from the four seed cultivators is very efficient, because the value for farmers reaches 100%. In channel II, the highest yield for farmers is 75%, then 70% and the lowest is 52%.